1988
DOI: 10.1111/j.1365-2125.1988.tb05289.x
|View full text |Cite
|
Sign up to set email alerts
|

Ebastine: the effect of a new antihistamine on psychomotor performance and autonomic responses in healthy subjects.

Abstract: 1 Ebastine, through its carboxylic acid metabolite has antihistamine (Hl-receptor) activity in man. 2 We have examined in a single blind placebo controlled study the effects of 10 mg and 50 mg of ebastine on cardiovascular, autonomic and psychomotor function in healthy subjects. 3 Ebastine had no effect on blood pressure or heart rate and there was no evidence of any anticholinergic activity on circulatory reflexes or salivation. 4 Ebastine did not impair psychomotor performance as assessed by critical fli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…Thus, RU may show a separation between the therapeutic dose and a dose likely to cause objective CNS impairment. Similar observations have earlier been made with terfenadine [14,18], astemizole [19], cetirizine [42] or ebastine [20]. The reason for the selective action of the therapeutic doses is not clear but may include factors such as lipid solubility or reflect a different mechanism of drug action at the periphery and in the CNS [23].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Thus, RU may show a separation between the therapeutic dose and a dose likely to cause objective CNS impairment. Similar observations have earlier been made with terfenadine [14,18], astemizole [19], cetirizine [42] or ebastine [20]. The reason for the selective action of the therapeutic doses is not clear but may include factors such as lipid solubility or reflect a different mechanism of drug action at the periphery and in the CNS [23].…”
Section: Discussionsupporting
confidence: 63%
“…These side-effects can interfere with the performance of daytime activities and not only place the patient at an increased risk of accidents in situations such as driving and operation of machinery, where high levels of alertness are required [17], but also reduce compliance with treatment regimens due to excessive fatigue and malaise. Clinical trials have consistently demonstrated that the second-generation antihistamines have a much more favourable therapeutic index and a significantly lower incidence of sedative effects than their predecessors and so represent a major advance in antihistamine therapy [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The borderline differences were occasionally found between placebo and ebastine, at separate test times or with the times combined, but the real differences were small and the significances partly result from different baseline values or from a statistical aoinflation. They could, however, refer to small concentrations of carebastine in the central nervous system, and since Vincent et al (1988b) reported impaired performance from larger doses of ebastine, it might be preferable to take daily doses in the evening. The effects of diazepam, though not very strong in the present trial, clearly differed from those recorded after placebo and ebastine.…”
Section: Discussionmentioning
confidence: 99%
“…Ebastine is well absorbed and extensively converted to its active carboxylic acid metabolite carebastine during the first pass through the liver. The elimination half-life of carebastine in man is 10 to 16 h (Vincent et al, 1988b); it is moderately accumulated during the treatment with therapeutic doses of ebastine once daily for 1 week, and the local responses to intradermal histamine are suppressed by over 50% for 24 h (Vincent et al, 1988b) with plasma concentrations of carebastine (100 ,ug 1-1) resulting from a daily dose of 20 mg ebastine.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ebastine were generally similar to those of placebo in tests of vigilance, cognitive performance, visual motor coordination, subjective estimates of drowsiness and driving performance (37,(81)(82)(83)(84). In one study, ebastine 10 mg caused a marginally significant increase in choice reaction time compared with placebo at 8 h after a single dose (95% CI for the difference 0.01-0.23), and a dose of 50 mg (2.5 times the maximum recommended dose) caused an increase in this parameter at 4 and 8 h (95% CI for the difference at both timepoints 0.01-0.25) as well as modest increases in indices of sedation (P < 0.05 vs placebo) (81). Neither dose affected critical flicker fusion.…”
Section: Cns Tolerabilitymentioning
confidence: 99%